Predatory publishing practices: is there life after Beall's list? - Nicholson, Denise Rosemary (WKW School of Communication & Information & NTU Libraries Nanyang Technological University, 2017)
Background. Scholarly communication is an ever-evolving practice. As publishing advanced from the printed format to digital formats, new trends, practices and platforms emerged in academia. As reputable publishers adapted their business models to accommodate open access, many non-reputable publishers have emerged with questionable business models and less-than favourable or unacceptable publishing services. Objectives. This paper discusses changing trends in scholarly publishing, the advent of and problems caused by pervasive predatory publishing practices, and possible solutions. The paper also investigates possible alternatives to Beall’s list and whether a “one-stop shop” black- or white list would serve as a comprehensive tool for scholarly authors. Results. The paper concludes that there is no “one-stop shop” or comprehensive resource or guidelines available at this stage for scholarly authors to consult before publishing. It alerts scholars to be cautious and to do research about potential publishers, before submitting manuscripts for publication. Contributions. It provides recommendations and some useful resources to assist authors before they publish their works.
Keywords: Predatory publishing; Open access publishing - Economic aspects; Scholarly electronic publishing - Economic aspects; Scholarly electronic publishing - Moral and ethical aspects